Translation and Interpreting in the Age of COVID-19 - Liu, Kanglong; Cheung, Andrew K. F. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents the latest developments in translation and interpreting (T&I), which has been at the forefront to face the challenges brought by COVID-19. The contributions in the book contain both quantitative and qualitative empirical studies as well as personal accounts of the impact and opportunities T&I has faced in the global pandemic, covering topics including metaphor translation, delivery of and access to T&I services during COVID-19, renewed perspectives on T&I practice and profession, and technological applications in the T&I classroom. The various themes in the book, through examining the role and many facets of T&I against the backdrop of COVID-19, have demonstrated that T&I as a vital means of intercultural communication is assuming immense importance at a time of uncertainties and disruptions. As one of the books addressing crucial issues of T&I at a time of global crisis, this edited book is of interest to many T&I professionals, researchers, teachers, and students who have been impacted by the pandemic and yet showed a continued interest in T&I and its future emerging practice in the post-pandemic era.
Translation and Interpreting in the Age of COVID-19: Challenges and Opportunities -- Metaphor Translation as Reframing: Chinese versus Western Stance Mediation in COVID-19 News Reports -- COVID-19 Translated: An Account of the Translation and Multilingual Practices Enacted in Hong Kong's Linguistic Landscape during the Pandemic Crisis Communication -- What is Chinese? A Case Study of the Chinese Translation of Government Guidance and Regulations in Relation to COVID-19 in the UK -- COVID-19 MT Evaluator: A Platform for the Evaluation of Machine Translation of Public Health Information Related to COVID-19 -- Remote Simultaneous Interpreting from Home or Hub: Accuracy of Numbers from English into Mandarin Chinese -- Remote Simultaneous Interpreting and COVID-19: Conference Interpreters' Perspective -- Reconceptualising Interpreting at the United Nations -- Humanitarian Interpreting in the Age of COVID-19 -- Teamwork in the Virtual Booth - Conference Interpreters' Experiences with RSI Platforms -- COVID-19 and the Configuration of Materiality in Remote Interpreting: Is Technology Biting Back? -- Hybrid Mode of Teaching in the Translation Classroom: Students' Perceptions and Experiences -- Unmasking the In-person Classroom: Cultural Advantages of Online Learning in the Chinese Context -- Teaching and Learning Translation and Interpreting in the Time of COVID-19: Preparation, Class Content and Activities and Assessment (The Slovak Case) -- Regrouping during COVID: Attitudes toward In-person and Remote Instruction in a Graduate Studies Program -- Teaching Interpreting in the Time of COVID: Exploring the Feasibility of Using Gather -- Use of Computer-Assisted Interpreting Tools in Teaching and Interpreting during COVID-19.
Keywords: Intercultural communication; Translating and interpreting; Computational linguistics; Communication in medicine; Language policy; Intercultural Communication; Language Translation; Computational Linguistics; Health Communication; Language Policy and Planning